2014
DOI: 10.4103/0975-7406.142951
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evidence for connection of nitric oxide-mediated pathways in neuroprotective mechanism of ischemic postconditioning in mice

Abstract: Introduction:Postconditioning (PoCo) is an adaptive phenomenon whereby brief repetitive cycles of ischemia with intermittent reperfusion instituted immediately after prolonged ischemia at the onset of prolonged reperfusion elicit tissue protection. PoCo is noted to exert a protective effect in various organs like heart, liver, kidney and brain. Various triggers, mediators and end effectors are suggested to contribute to the protective effect of PoCo. However, the neuroprotective mechanism of PoCo is poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The neurobehavioral impairment which followed I/R injury in the present study corroborates earlier reports (Gulati & Singh, 2014;Schimidt et al, 2014;Singh & Chopra, 2013;Surapaneni, T, Ansari, & Goli, 2017). Improvement of the behavioral impairment by pretreatment with Trévo™ indicates its ability to attenuate damaging cascades leading to the neurobehavioral dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…The neurobehavioral impairment which followed I/R injury in the present study corroborates earlier reports (Gulati & Singh, 2014;Schimidt et al, 2014;Singh & Chopra, 2013;Surapaneni, T, Ansari, & Goli, 2017). Improvement of the behavioral impairment by pretreatment with Trévo™ indicates its ability to attenuate damaging cascades leading to the neurobehavioral dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Another research also indicates that ischemic postconditioning exerts its neuroprotective effects via ROS suppression. A study involving rat models of local cerebral ischemia indicates that rapid initiation of ischemic postconditioning within 30 minutes of reperfusion reduces the levels of peroxides and lipid peroxides, in turn reducing free radical damage [ 7 , 70 ]. Furthermore, ischemic postconditioning has been shown to increase acetylcholine and NO synthesis and inhibit oxidative stress, thereby improving cognitive function ( Figure 4 ) [ 71 ].…”
Section: Signaling Molecules and Mechanisms In Conditioningmentioning
confidence: 99%
“…Additionally, it has already been suggested that the protective role of IPC in the liver is mediated through NO pathways [ 24 , 117 , 118 ] while there is evidence implicating NO in the protection of IPostC in tissues other than the liver [ 110 , 119 ]. Therefore, the protective effect of IPostC in liver IR injury could similarly be related to the enhanced level of expression of e-NOS and i-NOS, which in turn increase endogenous NO production [ 45 , 83 ].…”
Section: Mechanisms Of Hepatic Postconditioningmentioning
confidence: 99%